Frontières - Lévesque, Robert (CV Photo, 2001)
Lévesque quotes a poem by Lamartine to show that, from century to century, idealism collides with the notion of borders, the historical factor in wars and deaths. His text, inhabited by the figures of Gauguin, Camus, Barrès, Jacques Parizeau, Pessoa, Koltès, Rimbaud, and Ariel Sharon, is pessimistic. He notes that borders—geographical and mental, cultural and psychotic, technological, financial—are still tightly closed. The way to neutralize their lethal power, he writes, is to always feel and put oneself on the other side—something that has its own risks and perils.